Factors Influencing Diaphragmatic Compound Motor Action Potentials During Cryoballoon Ablation for Atrial Fibrillation. (19th September 2016) - SHARMA, PARIKSHIT S.; PADALA, SANTOSH K.; THOMPSON, J. JENKINS; GUNDA, SAMPATH; KONERU, JAYANTHI N.; ELLENBOGEN, KENNETH A.
Factors Influencing Diaphragmatic CMAP: Introduction: The diaphragmatic compound motor action potentials (CMAPs) have been used to predict and prevent phrenic nerve injury (PNI) during cryoballoon ablation of right pulmonary veins. We sought to assess factors that influence the amplitude of the surface CMAP recordings. Methods and Results: We analyzed CMAPs from consecutive patients undergoing cryoballoon ablation for paroxysmal atrial fibrillation. CMAP recordings were obtained using electrocardiography electrodes positioned in the "modified lead I" method while stimulating the right PN, until loss of capture (ascertained by palpation and fluoroscopy of the right hemi‐diaphragm). A total of 55 patients (age 63 ± 11 years; 60% men; body mass index [BMI] 31 ± 6) had adequate CMAP recordings and were included for evaluation of CMAP signals. CMAPs demonstrated 2 distinct components, an early higher amplitude signal (pacing artifact) and a later lower amplitude signal (true diaphragmatic CMAP). There was no significant change in the true CMAP recording amplitude with decrease in stimulus strength (P = 0.1). There was no impact of BMI on CMAP amplitude (P = 0.93). There was a significant phasic respiratory variation in CMAP amplitude with a mean decrease in CMAP amplitude of 10.8% (range: 8–12%) with inspiration lasting an average of 2 beats (P < 0.001). A decrease in CMAP amplitude of >30% was noted in 6 cases (11%) and termination of cryoablation prevented PNI. Conclusion: Diaphragmatic CMAP amplitude is not affected by stimulus strength or BMI. There is a significant respirophasic decrease in CMAP signal amplitude with inspiration. It is important to be aware of this variation to avoid premature termination of cryoablation.